Agrifound Parvati: new garlic for hills - Singh, R K; Dubey, B K; Gupta, R P (Indian Horticulture, 2019)
Garlic Agrifound Parvati is a new variety, developed for mid and higher hills. It is popular among farmers for higher yield and export. It is a long day type (240-270 days) and recommended for cultivation in Srinagar, Almora, Mukteshwar, Palampur and Ooty. Tested at different locations, its average yield is highest (188.76 q/ha), higher than G-384 (55.05%), NRCWG-4-CDS-14/ M-4 (121.19%), Phule Baswant (133.90%), NRCWG-3-CBS-6-7/M-3 (158.43%), Agrifound White (G-41) (163.19%), Yamuna Safed 3 (G-282) (81.36%), Mukteshwar Selection 2 (2.89%) and VLG 1, (201.58%).